2019
DOI: 10.9734/jesbs/2019/v31i330150
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Teacher-written Corrective Feedback in Second Language Writing Pedagogy in Secondary Schools, Bulilima, Zimbabwe

Abstract: This study investigated the teachers' practice on written corrective feedback as well as the students' response to it in a bid to find practical solutions to the problem of low performance in English composition writing at "O" Level in Zimbabwe. The study sought to find out the nature of corrective feedback that "O" Level students get from their composition teachers and how these students respond to it. In this qualitative research, seven informants ("O" Level students) were interviewed; the researchers used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Teacher feedback is an essential key in the writing process. Teacher feedback has been identified as very beneficial to improve the students' writing performances (Muchemwa et al, 2019) and as a characteristic of a successful teacher in various subjects and classes (Gan et al, 2018). Teacher feedback can be given in various forms such as direct or indirect, focus or unfocused, as well as oral or written, etc.…”
Section: A Teacher Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Teacher feedback is an essential key in the writing process. Teacher feedback has been identified as very beneficial to improve the students' writing performances (Muchemwa et al, 2019) and as a characteristic of a successful teacher in various subjects and classes (Gan et al, 2018). Teacher feedback can be given in various forms such as direct or indirect, focus or unfocused, as well as oral or written, etc.…”
Section: A Teacher Feedbackmentioning
confidence: 99%
“…However, effective feedback from teachers has been seen as the most valuable feedback. Many students cannot achieve the maximum benefit of teacher feedback when teachers often offer error codes unaccompanied by any description (Muchemwa et al, 2019). Previous studies have also shown that many students do not have a favorable view of the code or general remarks made by the teacher (Ferguson, 2011).…”
Section: A Teacher Feedbackmentioning
confidence: 99%
“…Feedback is critical for improving students' writing knowledge, skills, strategies, and motivation (Graham et al, 2015). However, students cannot fully benefit from teacher feedback since teachers usually deliver mistake codes without providing context (Muchemwa et al, 2019). As a result, students have few opportunities to receive feedback on their written work.…”
Section: Introductionmentioning
confidence: 99%